2013
DOI: 10.1016/j.jiph.2012.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of exposure to ethanol vapors released during use of Alcohol-Based Hand Rubs by healthcare workers

Abstract: Ethanol concentrations were similar for these two exposure assessment methods and demonstrated a relationship between handled doses and inhaled doses. However, the ethanol vapors released during hand disinfection were safe for the healthcare workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…In a similar study with a larger sample of 86 healthcare workers tested before and after a 4‐hour shift, alcohol was not detected in blood and urine, but approximately one‐third of healthcare workers demonstrated an elevated mean expired EtOH level of 0.008 mg/dl within 2 minutes of exposure (Ahmed‐Lecheheb et al., ). Furthermore, another study found a significant positive correlation between the amount of hand sanitizer used and EtOH concentration in inhaled air, suggesting that increased sanitizer use will increase inhaled alcohol exposure (Hautemaniere et al., 2013b).…”
Section: Resultsmentioning
confidence: 99%
“…In a similar study with a larger sample of 86 healthcare workers tested before and after a 4‐hour shift, alcohol was not detected in blood and urine, but approximately one‐third of healthcare workers demonstrated an elevated mean expired EtOH level of 0.008 mg/dl within 2 minutes of exposure (Ahmed‐Lecheheb et al., ). Furthermore, another study found a significant positive correlation between the amount of hand sanitizer used and EtOH concentration in inhaled air, suggesting that increased sanitizer use will increase inhaled alcohol exposure (Hautemaniere et al., 2013b).…”
Section: Resultsmentioning
confidence: 99%
“…Similar contamination of exhaled breath by alcohol can occur if vapours of anti-freeze alcoholbased washer fluids from windshield washer permeates the automobile's cabin [21]. Another ways, how the environmental alcohol vapours can affect breath analysis, are false-positive results after using an alcohol-based hand disinfectant lotion prior the test [22][23]. All these cases signalise the "alcohol air-pollution" nearby the subject being tested, directly influencing the results.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 In a formal extension to their work, they detected significant levels of ethanol vapour in the air around the entrance to the airway during use of alcohol hand gel. 17 We also informally explored the hypothesis of breath contamination by simulating various gel application scenarios. We found that an individual could produce a positive breathalyzer result after just one gel application (data not shown) by rubbing their hands with gel close to their airway or by incidentally rubbing their face with gel on their hands.…”
Section: Discussionmentioning
confidence: 99%